2017
DOI: 10.1186/s11671-017-2201-y
|View full text |Cite|
|
Sign up to set email alerts
|

Investigations of Heavy Metal Ion Sorption Using Nanocomposites of Iron-Modified Biochar

Abstract: Magnetic biochar nanocomposites were obtained by modification of biochar by zero-valent iron. The article provides information on the impact of contact time, initial Cd(II), Co(II), Zn(II), and Pb(II) ion concentrations, dose of the sorbents, solution pH and temperature on the adsorption capacity. On the basis of experiments, it was found that the optimum parameters for the sorption process are phase contact time 360 min (after this time, the equilibrium of all concentrations is reached), the dose of sorbent e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 49 publications
1
27
0
Order By: Relevance
“…The band in the range of 2,850-3,021 cm -1 is due to the aliphatic C-H stretching [24]. The band in the range of 2,000-2,200 cm -1 is due to the triple bonds of alkynes and 1540-1570 cm −1 is due to the C=O and C=C aromatic vibrations in ring [25]. The band seen at 1396-1403 cm -1 indicates deformation stretching of the -CH, -CH 2 and -CH 3 functional groups [23].…”
Section: Characterizations Of the Adsorbentsmentioning
confidence: 97%
See 1 more Smart Citation
“…The band in the range of 2,850-3,021 cm -1 is due to the aliphatic C-H stretching [24]. The band in the range of 2,000-2,200 cm -1 is due to the triple bonds of alkynes and 1540-1570 cm −1 is due to the C=O and C=C aromatic vibrations in ring [25]. The band seen at 1396-1403 cm -1 indicates deformation stretching of the -CH, -CH 2 and -CH 3 functional groups [23].…”
Section: Characterizations Of the Adsorbentsmentioning
confidence: 97%
“…The adsorption of Cr(VI) at different concentrations plays an important role in determining the adsorption capacity of the adsorbent. Cr(VI) solutions adjusted to pH 2.0 at different concentrations (8,25,58,80,98,131,158,171,191 mg/L) were added to the optimum amounts of adsorbents and the mixtures were stirred for 2 h. The equilibrium relationships between the adsorbents and Cr(VI) were eval-uated using Freundlich, Langmuir, Scatchard, Dubinin-Radushkevich (D-R) and Temkin isotherm models [16,[18][19][20][21]. Adsorption isotherms and effect of the concentration on the percentage of Cr(VI) removal are depicted in the Fig.…”
Section: Adsorption Isothermsmentioning
confidence: 99%
“…Historically, biochars have been used in agriculture to improve soil fertility [1,2]. As porous materials, biochars or their derived activated carbons (ACs) find applications in water purification processes such as removal of heavy metal ions [3][4][5], organic compounds [6,7], and other pollutants [8].…”
Section: Introductionmentioning
confidence: 99%
“…At higher pHs, the sorption capacity values would decrease because the metal ions would start to hydrolyze and precipitate. 32 The Cd and Pb for instance can precipitate at high pH solution (pH > 7 for Cd and pH > 5 for Pb) as stated by Ding et al 33 Park et al 34 indicated that the metal precipitation can be avoided at pH less than 7. On the other hand, the adsorption of some analyzed cations can be lower at low pH due to electrostatic repulsion between the BC surface and the cations.…”
Section: Experiments With Activated Carbonmentioning
confidence: 97%